2017
DOI: 10.3390/app8010036
|View full text |Cite
|
Sign up to set email alerts
|

PHD and CPHD Algorithms Based on a Novel Detection Probability Applied in an Active Sonar Tracking System

Abstract: Underwater multi-targets tracking has always been a difficult problem in active sonar tracking systems. In order to estimate the parameters of time-varying multi-targets moving in underwater environments, based on the Bayesian filtering framework, the Random Finite Set (RFS) is introduced to multi-targets tracking, which not only avoids the problem of data association in multi-targets tracking, but also realizes the estimation of the target number and their states simultaneously. Usually, the conventional Prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…An automotive application of the PHD filter is presented in [14] where vehicles are tracked using features extracted from a monocular camera. Chen et al reported an underwater tracking application of the PHD and CPHD filters wherein the state-dependent probability of detection values is calculated from a sonar model [15].…”
Section: Related Workmentioning
confidence: 99%
“…An automotive application of the PHD filter is presented in [14] where vehicles are tracked using features extracted from a monocular camera. Chen et al reported an underwater tracking application of the PHD and CPHD filters wherein the state-dependent probability of detection values is calculated from a sonar model [15].…”
Section: Related Workmentioning
confidence: 99%
“…Underwater multi-object tracking while moving is another interesting problem in active sonar systems. Chen et al proposed to improve the conventional probability hypothesis density (PHD) and cardinalized PHD (CPHD) algorithms for an active acoustic tracking system in [18]. Particularly when the detection probability is not available as a priori, it is necessary to estimate simultaneously the number of multi-targets, the detection probability, and their states.…”
Section: Underwater Target Detection and Localizationmentioning
confidence: 99%
“…It can also solve the tracking difficulties caused by uncertain factors, such as detection parameters and new targets in the environment with an unknown clutter rate [7][8][9]. The filtering technology developed by RFS has been used in many successful applications, such as aerial warning [10], marine monitoring [11,12], computer vision [13] and sonar detection [14].…”
Section: Introductionmentioning
confidence: 99%